Protective Mechanism of Blood-brain Barrier of Cerebral Hemorrhage Model Rats with Different Acupuncture Manipulation Duration - Xiaozhuo SUN; Zhuolin YANG; Zhihong MENG (康复学报)
Objective:To explore the effect of different acupuncture manipulation duration on the blood-brain barrier tight junction protein in rats with cerebral hemorrhage.Methods:A total of twenty SD male rats were divided into sham-operated group, model group, acupuncture 5s group and acupuncture 60s group by random number table method, with 5 rats in each group. Caudate nucleus autologous blood injection was used in cerebral hemorrhage model. After the establishment of cerebral hemorrhage model, the acupuncture groups received acupuncture on"shuigou"point and bilateral"neiguan"points, and received acupuncture on 5s or 60s every day. The sham-operated and model groups did not receive acupuncture. Five days later, the expressions of Occludin, Claudin-5 and JAM-1 immunofluorescence positive cells in the cerebral hematoma area of rats under light microscope(×400)were compared.Results:(1)Expression of Occludin immunofluorescence positive cells:Compared with the sham-operated group, the Occludin expression in the model, acupuncture 5s and 60s groups decreased significantly(P<0.05). Compared with the model group, the Occludin increased both in the acupuncture 5s and 60s groups. The increase was more significant in the 60s acupuncture group(P<0.05);(2)Expression of Claudin-5 immunofluorescence positive cells:Claudin-5 physiological expression was in the sham-operated group. Compared with the sham-operated group, the Claudin-5 expression in the model group, acupuncture 5s and 60s groups were significantly reduced(P<0.05). Compared with the model group, Claudin-5 in the 5s and 60s acupuncture groups increased(P<0.05);(3)Expression of JAM-1 immunofluorescence positive cells:JAM-1 was physiologically expressed in the sham-operated group. Compared with the sham-operated group, the expression of JAM-1 in the model, acupuncture 5s and 60s groups were significantly decreased(P<0.05). Compared with the model group, the expression of the acupuncture 5s group was not significant(P>0.05). The JAM-1 level in the acupuncture 60s group increased significantly(P<0.05).Conclusion:Long-time acupuncture has a positive effect on the protection of the blood-brain barrier after cerebral hemorrhage and can increase the permeability of the blood-brain barrier.